2016
DOI: 10.1007/s10903-015-0310-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Recruitment and Adherence in a Randomized Controlled Diet and Exercise Weight Loss Intervention Among Minority Breast Cancer Survivors

Abstract: Minority recruitment to cancer trials is low and there are limited data on minority adherence to lifestyle modification interventions. We examined factors related to recruitment and adherence to a pilot weight loss intervention among Hispanic and black breast cancer survivors. Participants completed a detailed screening interview to assess barriers to enrollment. An index was created to assess adherence at 6 months. 112 potentially eligible women were identified; 66 consented and completed a screening intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 40 publications
2
35
1
1
Order By: Relevance
“…Furthermore, most health care professionals do not receive adequate training in how to operationalize health behavior recommendations at the level of an individual patient, so a generalized lack of expertise or competency in knowing what and how to recommend changes is a major barrier. Providers also need resources for appropriate services (eg, dietitians, exercise specialists, or programs); but a lack of supportive infrastructure, including lack of access to appropriate referrals or effective strategies as well as limited insurance coverage, can inhibit provider recommendations . Care providers also may be skeptical that a cancer survivor can change behavior or may worry that engaging in weight management or PA during or after treatment may be risky to the survivor's overall health .…”
Section: Opportunities and Challenges For The Workforce Care Coordinmentioning
confidence: 99%
“…Furthermore, most health care professionals do not receive adequate training in how to operationalize health behavior recommendations at the level of an individual patient, so a generalized lack of expertise or competency in knowing what and how to recommend changes is a major barrier. Providers also need resources for appropriate services (eg, dietitians, exercise specialists, or programs); but a lack of supportive infrastructure, including lack of access to appropriate referrals or effective strategies as well as limited insurance coverage, can inhibit provider recommendations . Care providers also may be skeptical that a cancer survivor can change behavior or may worry that engaging in weight management or PA during or after treatment may be risky to the survivor's overall health .…”
Section: Opportunities and Challenges For The Workforce Care Coordinmentioning
confidence: 99%
“…Exercise programs have also been shown to enhance mental health-related quality of life (QoL) amongst breast cancer survivors who have completed cancer therapy [2,3]. However, some breast cancer survivors have low confidence and understanding towards the benefits of exercise to their cancer outcomes following treatments [4,5]. A number of psychological theories and techniques related to motivation have been used to understand and enhance exercise uptake and adherence in the population in general and cancer survivors in particular [6].…”
Section: Introductionmentioning
confidence: 99%
“…Adherence is particularly important because minority recruitment across cancer trials is low, and to the best of our knowledge there is scarce evidence regarding minority participation and adherence with lifestyle-modifiable interventions. 16 Spector et al 38 found that, in addition to globally lower participation in physical activity, Hispanic women reported more perceived barriers to exercise compared with white women. Hispanic women more often related a lack of knowledge regarding how to exercise, a lack of enjoyment from exercise, and discouragement as barriers to their participation, further explicating the significance of our 1-on-1, directly supervised trial in motivating participants and maintaining adherence to the study protocol.…”
Section: Discussionmentioning
confidence: 99%
“…10 MSY also is a long-term complication of curative treatment for many cancers, including breast cancer. 16,17 Of the 51 exercise trials for BCS successfully completed since 1989, few have specifically involved Hispanic patients. 12,13 As breast cancer survival rates continue to improve worldwide, there is an increasing focus on the role of modifiable risk factors in prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation